Augmentation of the anticancer activity of CYT997 in human prostate cancer by inhibiting Src activity - Yong Teng; Yafei Cai; Wenhu Pi; Lixia Gao; Chloe Shay (Journal of Hematology & Oncology, 2017)
Abstract Background Abnormalities of tubulin polymerization and microtubule assembly are often seen in cancer, which make them very suitable targets for the development of therapeutic approach against rapidly dividing and aggressive cancer cells. CYT997 is a novel microtubule-disrupting agent with anticancer activity in multiple cancer types including prostate cancer. However, the molecular mechanisms of action of CYT997 in prostate cancer have not been well characterized. Methods Src knockdown cells were achieved by lentiviral-mediated interference. The drug effects on cell proliferation were measured by MTS. The drug effects on cell viability and death were determined by Cell Titer-Glo® Luminescent cell viability kit and flow cytometry with Zombie Aqua™ staining. The drug effects on apoptosis were assessed by Cell Death Detection Elisa kit and Western blot with a cleaved PARP antibody. The drug effects on cell invasion were examined by Matrigel-coated Boyden chambers. Oxidative stress was detected by DCFH-DA staining and electrochemical biosensor. Mouse models generated by subcutaneous or intracardiac injection were used to investigate the in vivo drug efficacy in tumor growth and metastasis. Results CYT997 effectively inhibited proliferation, survival, and invasion of prostate cancer cells via blocking multiple oncogenic signaling cascades but not the Src pathway. Inhibition of Src expression by small hairpin RNA or inactivation of Src by dasatinib increased the CYT997-induced cytotoxicity of in vitro. Moreover, the combination of dasatinib and CYT997 exhibited a superior inhibitory effect on tumor growth and metastasis compared with either of the drugs alone. Conclusion Our findings demonstrate that blockage of Src augments the anticancer effect of CYT997 on prostate cancer and suggest that co-treatment of dasatinib and CYT997 may represent an effective therapeutic regimen for limiting prostate cancer.